Sociological concept of Ukrainian literature by Professor KhINO V. Koryak - Сподарець, Михайло Павлович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article discusses the features of the concept of Ukrainian literature teacher and professor of KhINO, the head of the department of the history of Ukrainian literature (1933–1936) of the Kharkov University V. Koryak (1889–1937). His aesthetic views combined Marxism, sociological criticism and the ideas of building “proletarian culture”. The sociological concept of the dynamics of the national literary process and the interpretation of works of art reflected the Marxist approach to the analysis of writing and significantly influenced the Ukrainian literary criticism of the 1920s, as well as its further transformations during the period of “socialist realism”. V. Koryak taught at KhINO since 1925, and having defended his thesis, he first became the so-called “red professor”, from 1927 - a visiting professor, while continuing to teach the course of history of Ukrainian literature. He was also the head of the Soviet literature room at the T. G. Shevchenko Institute of Literature, and from 1933 to 1936, after the restoration of Kharkov University, he headed the department of the history of Ukrainian literature. The basic terms of the sociological concept of V. Koryak were made public in the textbook of Ukrainian Literature (1928), which was used to teach this subject. This course was the first attempt to synthesize the problematic issues of "Marxist literary criticism" to create an original concept of the history of Ukrainian literature based on the sociological method. Negative and positive features of V. Koryak’s literary-critical concept were reflected to the greatest extent in his interpretation of T. G. Shevchenko’s works. A significant amount of his extraordinary ideas can also be traced in the interpretation of the works of other Ukrainian writers.